Evaluasi Kultivar Apel dan Zat Pengatur Tumbuh (Sitokinin-Auksin) Terhadap Tingkat Keberhasilan Eksplan Apel Secara In Vitro: Evaluation of Apple Cultivars and Growth Regulators (Cytokinin-Auxin) on The Success Rate of Apple Explants In Vitro - Hidayatullah, Careca Sepdihan Rahmat; Santoso, Untung; Nursandi, Fatimah; Simanjuntak, Rich Gemilang; Priliraningrum, Oentari (Agrocentrum, 2024)
Successful in vitro propagation can support the provision of large, fast and highquality apple seeds. Growth regulators commonly used in culture techniques are cytokinins and auxins. the addition of 4 ppm BAP to the culture media can increase the lipid content and biomass 1.26 times higher in microalgae. This study aims to evaluate the ability of apple cultivars and the growth regulators BAP (Benzyl amino purine) and IAA (Indole acetic acid) to regenerate apple shoots in vitro. The experimental design used RAK (randomized block design) 2 factors. The first factor was shoots from four apple cultivars, namely Fuji, Red delicious, gala, and manalagi. The media used were 1) MS + 3 mg/L BAP + 0.2 mg/L IAA, 2) MS + 6 mg/L BAP + 0.2 mg/L IAA, 3) MS + 3 mg/L BAP + 0.3 mg/L IAA, and 4) MS + 6 mg/L BAP + 0.3 mg/L IAA. Based on the percentage of live explants, apple shoots show a relatively high level of success in the Fuji apple cultivar for all BAP-IAA growth regulator compositions, namely 3 mg/L BAP + 0.2 mg/L IAA, 6 mg/L BAP + 0.2 mg/L IAA, 3 mg/L BAP + 0.3 mg/L IAA, and 6 mg/L BAP + 0.3 mg/L IAA. Apple cultivars and growth regulators did not show a significant effect on the percentage of live explants, green color of shoots, explant contamination and number of leaves. There is a need for further studies regarding the type of explant with the right type of cytokinin hormone to regenerate green shoots more optimally.